The impact of social media fashion influencers' relatability on purchase intention: The mediating role of perceived emotional value and moderating role of consumer expertise - Ji Wang; Yidan Ma; Le Min; Jiannan Geng; Yujia Xiao (Acta Psychologica)
With the rise of social media, social media fashion influencers (SMFIs) have become an important channel for brands to communicate with consumers, and their relatability plays an important role in promoting consumers' purchase intention. However, the impact of SMFIs' relatability on consumers' purchase decisions and its functional mechanism have not been fully explored. The study clarifies the concept of SMFIs' relatability, explores its dimensions, and examines its impact on consumers' purchase intention, with perceived emotional value as a mediator and consumer expertise as a moderator. This study employed quantitative methods to collect data from a sample of 324 consumers who have followed SMFIs in China. The results show that SMFIs' relatability has a direct and positive impact on consumers' purchase intention and has an indirect and positive impact on consumers' purchase intention through perceived emotional value. Consumer expertise negatively moderates the relationship between perceived emotional value and consumers' purchase intention. This study provides some insights into the relationship between SMFIs' relatability and consumers' purchase intention, and the functional mechanism and boundary condition behind it. This study provides guidance for SMFIs to optimize their content production around relatability to strengthen emotional connections with consumers. It also offers insights for brands on how to select SMFIs for collaboration and implement differentiated marketing strategies on the basis of consumer expertise.